Details of left ventricular remodeling and the mechanism of paradoxical ventricular septal motion after coronary artery bypass graft surgery. - Codreanu, I; Pegg, T; Selvanayagam, J; Robson, M; Rider, O; Dasanu, C; Jung, B; Taggart, D; Clarke, K; Holloway, C (2011)
OBJECTIVE: The purpose of this study was to obtain new details of three-dimensional left ventricular wall motion related to ventricular remodeling in patients undergoing coronary artery bypass graft (CABG) surgery. METHODS: Cardiac-gated, phase-contrast measurements using navigator-gated, high temporal resolution, tissue phase mapping were obtained on 19 patients (66 ± 7 years old) before and after CABG. Left ventricular motion patterns and myocardial velocities were recorded for radial, circumferential and longitudinal motion. Radial, circumferential and longitudinal velocity curves were obtained separately for 16 ventricular segments. Ventricular torsion rate and longitudinal strain rate were also derived pre- and post-surgery. RESULTS: After CABG, there was a significant improvement in apical contraction, with an apparent paradoxical decrease in the radial inward motion of the septal segments at the left ventricular base. Despite improved ventricular contractility during systole, peak longitudinal and rotational velocities decreased or showed no significant changes. An altered pattern of rotational motion with decreased initial counter-clockwise rotation at the beginning of systole and subsequent lower amplitude of reversed motions in diastole was also noted in most left ventricular segments. Lower peak clockwise rotational velocities were recorded in the basal anteroseptal segment with relatively higher values in the rest of the basal segments. CONCLUSION: Our results suggest that post-operative changes after CABG are limiting ventricular rotational and longitudinal motions, despite an increase in ventricular contractility due to revascularization. At the ventricular base, the restrained rotational motion of basal anteroseptal segment, located proximally to the right ventricular insertion, and higher rotational velocities of the rest of the segments are pushing the septum toward the right ventricle during ventricular twisting. At the ventricular apex, the restrain in rotational motion caused by post-operative adhesions is affecting all apical segments due to a much smaller left ventricular diameter at this level. The rotating apex and the apical septum are similarly displaced toward the right ventricle during ventricular twisting.